Black Phosphorus: Abnormal Near‐Infrared Absorption in 2D Black Phosphorus Induced by Ag Nanoclusters Surface Functionalization (Adv. Mater. 43/2018). Issue 43 (22nd October 2018) - Hu, Zehua; Li, Qiang; Lei, Bo; Wu, Jing; Zhou, Qionghua; Gu, Chengding; Wen, Xinglin; Wang, Junyong; Liu, Yanpeng; Li, Shisheng; Zheng, Yue; Lu, Junpeng; et al.
Abstract : In article number 1801931, Jinlan Wang, Wei Chen, and co‐workers develop a new strategy to enhance the near‐infrared absorption and optoelectronic performance of 2D black phosphorus via Ag nanoclusters functionalization. It is shown that Ag–P hybridization induces localized gap states, thus activating a new optical transition route in the near‐infrared region.